Corrosion related iron oxides: Cu, Mn and Cr doped hematite (2003)
We have obtained Cu, Mn, and Cr doped hematites, by a thermal treatment of doped goethites at 500 and 880 °C in air for 24 h. The goethites were prepared in the laboratory from iron chloride solutions in the presence of Cu^"^, Mn^^, and Cr^^ ions. The samples are characterized by Mossbauer spectroscopy and X-ray diffraction. It is found that at 500 °C all the goethites have transformed into hematites. However, the thermal treatment at 880 °C produces hematites with better crystallinity.